Peran Penting E-Business dan E-Commerce dalam Meningkatkan Daya Saing Pemasaran di Bank Syariah - Tiara Adelia Putri; Muhammad Iqbal Fasa (Jurnal Bersama Ilmu Ekonomi (EKONOM), 2025)
The development of digital technology has driven the transformation of Islamic banking, where e-business and e-commerce have become the main strategies in increasing marketing competitiveness. E-business integrates technology into bank operations, increases service efficiency, expands customer reach, and creates a more competitive banking ecosystem. In marketing, data-based digital strategies enable more specific customer segmentation and increase customer engagement. Meanwhile, e-commerce facilitates digital services such as mobile banking, online payments, and technology-based Islamic financing, which increase transparency and transaction security. Other advantages include expanding market reach, support for MSMEs, and the use of blockchain technology, smart contracts, AI, and big data analytics in increasing efficiency and personalization of services. However, challenges such as uneven digital infrastructure, low digital literacy, and evolving regulations need to be overcome. However, Islamic-based fintech and digital payment innovations open up great opportunities for Islamic banks to continue to grow and compete globally. Therefore, adaptive strategies and collaboration with the technology industry are needed to strengthen the competitiveness of Islamic banks.